A Putative fossil zygomycetous fungus with mantled zygosporangia and apposed gametangia from the lower coal measures (Carboniferous) of Great Britain - Harper, Carla (My University, 2013)
Several specimens of a new fungal reproductive unit, Halifaxia taylorii nov. gen. et spec., occur within the tracheids of a structurally preserved fern axis from the Lower Pennsylvanian of Great Britain. The reproductive units, which appear to be lateral outgrowths of tubular hyphae, consist of a mantled sphere (80–90 μm in diameter) borne terminally on an inflated subtending structure, which may also be mantled. A smaller element clasps the proximal portion of the subtending structure; one arm of this element extends further up along and appears to eventually fuse laterally with the subtending structure. The reproductive units are interpreted as zygosporangium-apposed gametangia complexes of a zygomycetous fungus. Although several structural features of H. taylorii resemble features seen in the zygosporangium-gametangia complexes of certain modern zygomycetes, the precise systematic affinities of the fossils remain unresolved. Nevertheless, the discovery is important because it provides new information on the morphology and evolutionary history of the zygomycetous fungi, which are poorly resolved on the basis of fossils.
PUBLISHED
Keywords: Smart & Sustainable Planet; CARBONIFEROUS; FOSSIL; Fossil Fungi; Mucoromycotina; United Kingdom (Great Britain & Northern Irel; Zygomycota